Peran Orang Tua dan Pendampingan Pembelajaran Jarak Jauh Pada Masa Pandemi - Sukatin; Fitri Nasution (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2021)
The occurrence of the Covid-19pandemic around the world has resulted in changes in various lives, including in the field of education. The government policy requiring studying from home, working from home and praying at home in the first week felt very sudden. And make the confusion of parents and teachers compounded by the lack of preparation for distance learning. As learning materials at home, assignments from student books are given. During this pandemic, more children will be at home, this is an effort made to break the chain of the spread of Covid, which has not yet subsided, even continues to grow. For the effectiveness of learning at this time the role of parents is very important, because the responsibility for education that is usually held by teachers while in school now completely shifts to both parents. Parents must accompany their children more in learning, be more attentive during learning, because when children are given freedom during unsupervised learning, not a few children take the opportunity to play online games, surf in cyberspace such as playing Facebook, Instagram, and other interesting applications, because in the learning process children are facilitated with cellphones plus a quota package that makes it easy to access whatever they want. For this reason, supervision and cooperation between parents and teachers is needed in continuing children's education.